Observed supersymmetry of hadrons and the tachyonless string models - Dey, Jishnu; Dey, Mira; Tomio, Lauro [UNESP] (Elsevier, 1992)
The experimental mesonic density of states ρmeson(m)≃ρbaryon(m) from 0.9 to 1.3 GeV. In this region the ρmeson fits the ρ(m) deduced for it from discrete bag model states. Beyond 1.3 GeV one can expect exotic mesons. If ρmeson is replaced by the baryon density (as suggested by string model studies [D. Kutasov and N. Seiberg, Nucl. Phys. B 358 (1991) 600; P.G.O. Freund and J.L. Rosner, Phys. Rev. Lett. 68 (1992) 765]), agreement with theory is obtained up to 1.7 GeV. Beyond 1.7 GeV exotic baryons may be expected.